Nematode microRNAs can Individually Regulate Interferon Regulatory Factor 4 and mTOR in Differentiating T Helper 2 Lymphocytes and Modulate Cytokine Production in Macrophages - Soichot, Julien; Guttmann, Nathalie; Rehrauer, Hubert; Joller, Nicole; Tritten, Lucienne (Frontiers in Molecular Biosciences, 2022)
Parasitic nematodes are masterful immunomodulators. This class of pathogens has evolved a spectrum of sophisticated strategies to regulate and evade host immune responses, mediated through the release of various molecules. In this context, the release of microRNAs (miRNAs), short post-transcriptional regulators of gene expression, has been of particular interest in the host-parasite interplay. Evidence that parasite-derived miRNAs modulate host innate and adaptive immune responses has become increasingly compelling. However, since miRNAs are usually contained in extracellular vesicles containing other mediators, it is difficult to assign an observed effect on host cells to miRNAs specifically. Here, the effects of some abundantly secreted miRNAs by nematodes used as models of gastrointestinal infections (Heligmosomoides polygyrus bakeri, Trichuris muris and Ascaris suum) were evaluated, addressing the potential of parasite miRNAs to impair in vitro differentiation of two important types of immune cells in the context of helminth infections, Th2 lymphocytes and macrophages. Mimicking a continuous exposure to low concentrations of nematode miRNAs, the interferon gamma signaling, the IL-2/STAT5 signaling, and the mTOR signaling pathways were identified as downregulated by Hpo-miR-71-5p. Interferon regulatory factor 4 (Irf4) was validated as a target of Hpo-miR-71-5p, while Mtor is targeted by Asu-miR-791-3p, abundant in the T. muris secretions. By trend, Hpo-miR-71-5p impacts mildly but consistently on the amounts of inflammatory cytokines in unpolarized macrophages but leads to slightly increased IL-10 level in alternatively activated cells. In addition, our data suggests that transfected miRNAs remain for days in recipient cells, and that Hpo-miR-71-5p can incorporate into mouse Argonaute protein complexes. Nematode miRNAs can impair both innate and adaptive arms of host immunity. Hpo-miR-71-5p in particular, absent in mammals, interacts with host genes and pathways with crucial involvement in anthelmintic immune responses. This report brings new insights into the dynamics of miRNA-driven immunomodulation and highlights putative targeted pathways. Although the absolute repression is subtle, it is expected that the dozens of different miRNAs released by nematodes may have a synergistic effect on surrounding host cells.